IMPLEMENTING HOTS-BASED INTERACTIVE QUIZZES ORIENTED ON LOCAL WISDOM THROUGH QUIZIZZ APPLICATION AT ELEMENTARY SCHOOLS - Tyas Deviana; Nawang Sulistyani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The Covid-19 pandemic caused the need for adaptation in all areas, including the field of education. Online learning was the way to adapt to the pandemic. Many institutions increased their human resources through training for the preparation of online learning tools. The result was that the teachers were able to make HOTS-based interactive quizzes oriented on local wisdom in Kab. Tulungagung through the Quizizz application and its implementation. The goal was that interactive quizzes through the Quizizz application could be applied and provide benefits to online learning. This study aimed to analyze the implementation of HOTS-based interactive quizzes oriented on local wisdom in Kab. Tulungagung. The scope of this research included question making, interactive quiz implementation, and evaluation. The study involved 25 students in grade V at SDN Mojosari 1 consisting of 11 male and 14 female students. The process of making evaluation questions started from making the question lattice then converting it into multiple-choice questions by paying attention to HOTS based on local wisdom in Kab. Tulungagung. The implementation of the interactive quiz resulted in the effectiveness of the interactive quiz by 88%. The result of the evaluation of HOTS interactive quiz implementation based on local wisdom in Kab. Tulungagung found that: 1) interactive quizzes through the Quizizz application were needed as an online learning assessment instrument; 2) the use of interactive quizzes eased the teachers to provide assessments without having to make manual corrections as well as being able to analyze the questions made; 3) it fostered competition between students.